Analysis of Muzara’ah-Based Productive Waqf's Impact on the Welfare Community in the Bireuen District - Mukhlish Muhammad Nur; Munardi Munardi; Rayyan Firdaus; Mulyana Mulyana (Jurnal Ilmiah Ekonomi Islam, 2023)
Bireuen District has the second largest land waqf asset in Aceh Province. These assets have been distributed for the benefit of mosques, prayer rooms, schools, cemeteries, Islamic boarding schools, and other social services, while the poverty rate in Bireuen Regency is still relatively high. In other historical and empirical studies, it was found that waqf has played a role in economic and other social development. Thus, this study aims to analyze the effect of muzaraah-based productive waqf financing on the community in the Matang Panyang Settlement, Peusangan District, Bireuen Regency. This research is quantitative research with a comparative method using primary data obtained by distributing questionnaires to 30 respondents who were selected using a purposive sampling technique. The data analysis technique used was the Wilcoxon Matched-Paired Signed Test with the help of SPSS. Based on the Wilcoxon Statistical Test, it was found that the Z value was -4.810 with a significant level of 0.000. This shows that there is a significant difference between income before being given productive waqf and after being given productive waqf capital. Where the average income before getting productive waqf financing is Rp. 468,333.33 and increased to Rp. 943,333.33 after obtaining productive waqf financing